Effect of Gibberllic Acid, Sulphuric Acid, Thiourea and Potassium Nitrate on Seed Germination and Seedling Growth of C. Sempervirens L. Pyramidalis and C. Sempervirens L. Horizontalis - A. El-Malki, Nadia; . El-Bakkosh, Ali (Scientific Journal of University of Benghazi, 2026)
As a result of presence of dormancy phenomena in the seeds of the two species of cupressus trees, C. sempervirens L. Pyramidalis and C. sempervirens L. Horizontalis which grown well in green mountain area. Because of the importance of these trees that subjected to extinction in it's natural habitat, like many other trees grown in the green mountain. This study has been carried out to investigate the efficiency of using different concentration from the growth regulator "gibberellic acid", concentrated sulphuric acid and some germination promotion chemicals like thiourea and potassium nitrate, on breaking of their seed dormancy and promotion of seedling growth. The results showed that the highest percentage of seed germination and seedling development were obtained by treating C. sempervirens L. Horizontalis seeds with concentrated sulphuric acid for 10 min followed by treatment with 100 ppm gibberellic acid for 24 hours. While in case of C. sempervirens L. Pyramidalis seeds, treating with concentrated sulphuric acid for 10 min followed with 50 ppm of gibberellic acid or with potassium nitrate (0.2 %) for 24 hours showed the highest percentage of seed germination and maximum development of seedling. However the concentration 400 ppm of thiourea and gibberellic acid inhibited germination and development of both variety seedlings significantly in compared with other treatments including untreated seeds. Finally results showed that there were no significant differences between treatments in calculated mean germination time for the seeds of all species used.